Effect of a Nurse-Led Community Health Worker Intervention on Latent Tuberculosis Medication Completion Among Homeless Adults. Issue 6 (November 2021) - Nyamathi, Adeline; Salem, Benissa E.; Shin, Sanghyuk S.; Jones, Adrianna A.; Garfin, Dana R.; Yadav, Kartik; Chang, Alicia H.; White, Kathryn; Morisky, Donald
Abstract : Background: Tuberculosis (TB) disproportionately affects marginalized and impoverished homeless adults. Although active TB can be prevented by treating latent TB infection (LTBI), individual factors, such as high prevalence of depression and anxiety, drug and alcohol use, and unstable housing, lead to poor LTBI treatment adherence and completion among homeless adults. Objectives: We hypothesized that the delivery of a tailored nurse-led, community health worker (RN/CHW) program across the LTBI continuum of care (e.g., screening, diagnosis, and treatment) that delivers 3HP treatment (3HP: rifapentine plus isoniazid) for homeless adults (e.g., sheltered and unsheltered) and is tailored to their health and social service needs will overcome existing treatment completion barriers. We also hypothesized that mental health symptoms (e.g., depression and anxiety), drug use score, and problematic alcohol use will decline over time among clients receiving this treatment. Methods: We assessed the effect of delivering a theoretically guided, RN/CHW-based, single-arm study among eligible LTBI-positive homeless adults ( N = 50) on completion of a weekly, directly observed, 12-dose 3HP LTBI treatment in Central City East (Skid Row). Completing 3HP treatment was compared to the only known historical, clinic-based control that obtained 65% completion among homeless adults. Secondary outcomes included drug and alcohol use, depression, and anxiety. Results: The RN/CHW program achieved a 91.8% 3HP treatment completion rate among homeless adults. Younger homeless adults (<50 years old) were less likely to complete 3HP treatment compared to those who were older. Neither drug use, depression, nor anxiety was associated with 3HP treatment completion. Decrease in anxiety was observed at 3 months, but not at 6 months, compared to baseline. Discussion: To our knowledge, the pilot study is the first to evaluate an effective RN/CHW-delivered, community-based intervention, which can reduce the burden of active TB for homeless adults.